Enhancing anti-tumor immunity through liposomal oxaliplatin and localized immunotherapy via STING activation - Gu, Zili; Hao, Yang; Schomann, Timo; Ossendorp, Ferry; ten Dijke, Peter; Cruz, Luis J. (Journal of controlled release, 2023)
The cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway is a promising approach for anti-cancer immunotherapy by bridging innate and adaptive immunity. Recent evidence suggests that chemotherapy-induced DNA damage can directly induce dendritic cell (DC) maturation and recruitment, which synergizes with STING activation to enhance anti-tumor effects. As an immunogenic cell death (ICD) inducer, oxaliplatin generates massive double-stranded DNA (dsDNA) crosslinks, release of tumor-associated antigens and promoting the “eat me” signal. STING activation improves antigen immunogenicity, which can promote T cell activation and infiltration. In this study, we developed liposomes encapsulating oxaliplatin and combine this formulation with a STING agonist (ADU-S100) for treating colorectal cancer. The liposomes efficiently inhibited the proliferation of tumor cells while induced ICD in CT26 colorectal cancer cells, which enhanced dendritic cell maturation and phagocytosis in vitro. The liposome-based immunochemotherapy exhibited the strongest efficacy, resulting in complete remission upon tumor inoculation. Mechanistic studies showed this potent anti-cancer effect was related to the significant recruitment of infiltrating CD8 and CD4 T cells, reduction of suppressive Treg cells, and a shift in the phenotype of tumor-associated suppressive macrophages that promote cancer to immune stimulating macrophages. Thus, our study demonstrated the potential of combining oxaliplatin-loaded liposomes with a STING agonist to reduce tumor growth by regulating the immunosuppressive state in the tumor. [Display omitted] •First combination of oxaliplatin and ADU-S100 for cancer treatment•Enhanced anti-tumor efficiency by regulate tumor microenvironment•Orchestrated immune response on both innate and adaptive immunity